Tai Chi Intervention Increases Progenitor CD34+ Cells in Young Adults. Issue 4 (May 2014) - Ho, Tsung-Jung; Ho, Li-Ing; Hsueh, Kuo-Wei; Chan, Tzu-Min; Huang, Shih-Li; Lin, Jaung-Geng; Liang, Wen-Miin; Hsu, Wei-Hung; Harn, Horng-Jyh; Lin, Shinn-Zong
Tai Chi has been shown to have many great health benefits. However, few research attempts have been made to explore the effects of practicing TCC on life span. This study provides direct evidence of Tai Chi's antiaging effects. We conducted a retrospective cross-sectional study to compare the rejuvenating and antiaging effects among Tai Chi group (TCC) and brisk walking group (BW) and no exercise habit group (NEH). Thirty-two participants were selected out of a possible 60 based on a survey, and they were separated into three groups: the TCC group (practicing for more than 1 year), the BW group (practicing for more than 1 year), and the NEH group. The CD34 + cell counts in peripheral blood of the participants was determined, and the Kruskal–Wallis test was used to evaluate and compare the antiaging effects of the three groups. Of the 32 participants in this study, the participants in the TCC group ( N = 10) outperformed the NEH group ( N = 12) with respect to the number of CD34 + progenitor cells. No significant difference was found between the TCC group and the BW group. TCC practice sustained for more than 1 year may be an intervention against aging as effective as BW in terms of its benefits on the improvement of CD34 + number.